2017
DOI: 10.3349/ymj.2017.58.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Hypomethylation ofSolute Carrier Family 6 Member 12Promoter Induces Metastasis of Ovarian Cancer

Abstract: PurposeOvarian cancer (OC) is the most fatal of gynecological malignancies with a high rate of recurrence. We aimed to evaluate the expression of solute carrier family 6, member 12 (SLC6A12) and methylation of its promoter CpG sites in a xenograft mouse model of metastatic OC, and to investigate the regulatory mechanisms that promote aggressive properties during OC progression.Materials and MethodsExpression of SLC6A12 mRNA was determined by reverse-transcription quantitative polymerase chain reaction (RT-qPCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
1
11
0
2
Order By: Relevance
“…Several new studies have suggested that hypomethytlation and increased expression of potential proto-oncogenes predict more aggressive and metastatic OC with a potentially lower survival. This has been seen for GABRP, SLC6A12, MGAT3, CT45, CA9, MUC13 and AGR2 (85)(86)(87)(88)(89)(90)(91).…”
Section: Potential Of Dna Methylation In Oc Prognosticssupporting
confidence: 53%
“…Several new studies have suggested that hypomethytlation and increased expression of potential proto-oncogenes predict more aggressive and metastatic OC with a potentially lower survival. This has been seen for GABRP, SLC6A12, MGAT3, CT45, CA9, MUC13 and AGR2 (85)(86)(87)(88)(89)(90)(91).…”
Section: Potential Of Dna Methylation In Oc Prognosticssupporting
confidence: 53%
“…Additionally, SLC6A8 has been shown to be related to aspects of the nervous system such as behavior (13), learning (14), and intelligence (15). Notably, many members of the GABA family have been confirmed to be involved in the occurrence and development of tumors (16)(17)(18). Loo et al found that SLC6A8 can promote brain-type creatine kinase-mediated colon cancer metastasis (19).…”
Section: Original Articlementioning
confidence: 99%
“…The expression levels of ITGA10 , a biomarker of type II diabetes mellitus ( Wang et al, 2021 ), are associated with metastasis in skin cutaneous melanoma ( Nurzat et al, 2021 ). SLC6A12 is a key gene that promotes aggressive metastasis during ovarian cancer progression ( Sung et al, 2017 ). SMAD4 loss is a biomarker of squamous cell carcinoma and is used for its prognosis and prediction of treatment response ( Hernandez et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%